Sponsorship of junior sport development programs in Australia - Wendy L. Watson; Rebecca Brunner; Lyndal Wellard; Clare Hughes (Elsevier, 2016)
Abstract Objective: This study investigated the nature and extent of unhealthy food, beverage, alcohol and gambling sponsors of children's sport development programs. Methods: Websites of junior development sport programs (n=56) associated with sporting organisations that received funding from the Australian Sporting Commission were analysed. Sponsors were considered unhealthy if they were alcohol or gambling companies or sold food and/or beverages that failed independent nutrition criteria. The websites of the sport development programs were also analysed for types of promotion. Results: There were 246 sponsors identified. Eleven (4.5%) sponsors were food, beverage, alcohol or gambling companies of which 10 (91%) were unhealthy. Surf Lifesaving (n=4) and athletics (n=3) websites had the highest number of unhealthy sponsors. Promotions associated with unhealthy sponsorship included logo placement on homepages (100%), naming rights (31%), logo on sport uniforms (27%) and branded participant packs (31%). Conclusions: The majority of food and beverage company sponsors in sport development programs are companies associated with unhealthy products. Two websites hosting junior development program information included an alcohol company sponsor and a gambling company sponsor. Implications: Unhealthy product sponsorship of children's sport should be addressed as part of a comprehensive regulation designed to reduce exposure to marketing of unhealthy foods.